2020
DOI: 10.1371/journal.pntd.0007933
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus-neutralising antibodies in healthy, unvaccinated individuals: What do they mean for rabies epidemiology?

Abstract: Rabies has been a widely feared disease for thousands of years, with records of rabid dogs as early as ancient Egyptian and Mesopotamian texts. The reputation of rabies as being inevitably fatal, together with its ability to affect all mammalian species, contributes to the fear surrounding this disease. However, the widely held view that exposure to the rabies virus is always fatal has been repeatedly challenged. Although survival following clinical infection in humans has only been recorded on a handful of oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 105 publications
0
52
0
Order By: Relevance
“…Whereas rabies is generally seen as an inevitable fatal disease, this idea is challenged by some studies that found rabies antibodies in serum of unvaccinated populations living in endemic areas [ 29 ]. The studies are limited—as populations with high exposure to possible rabies-infected wildlife are often hard to reach—and heterogeneous due to the variance in serological assays and used cut-offs [ 30 ]. DBS sampling provides solutions for both issues, and could therefore contribute to the understanding of the immunopathology of rabies in seropositive populations.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas rabies is generally seen as an inevitable fatal disease, this idea is challenged by some studies that found rabies antibodies in serum of unvaccinated populations living in endemic areas [ 29 ]. The studies are limited—as populations with high exposure to possible rabies-infected wildlife are often hard to reach—and heterogeneous due to the variance in serological assays and used cut-offs [ 30 ]. DBS sampling provides solutions for both issues, and could therefore contribute to the understanding of the immunopathology of rabies in seropositive populations.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, although rabies in FBs has been reported since 2012, no human cases have been documented [ 25 ]. The high percentage (69.6%) of rabies seroconversion in FBs suggests that the occasional exposure of FBs to RABV may cause peripheral abortive infection rather than rabies development in the central nervous system [ 10 , 26 ]. Therefore, rabies pathogenesis and the potential threat of asymptomatic infections in FBs must be further studied [ 26 ].…”
Section: Rabies In Fbsmentioning
confidence: 99%
“…Bats have similar or longer lifespans (e.g., up to 15 years for wild common vampire bats [51]) than currently vaccinated carnivores (e.g., up to 12 years for wild red foxes [52]), but 3-to 6-fold slower reproduction, which would extend vaccine-induced population immunity to a point that effective herd immunity may prevent transmission definitively [53,54]. Moreover, naturally acquired VNAs from sublethal exposures potentially creates substantial baseline immunity not observed for carnivore reservoirs, which may also help reach effective herd immunity faster [55]. Existing recombinant viral vaccines using vaccinia [56,57] and raccoonpox [58,59] vectors are immunogenic and protective in bats.…”
Section: Improving Managementmentioning
confidence: 99%